Psychoeducational Assessment and Report Writing - Dombrowski, Stefan C. (Springer, 2015)
This book is designed to help graduate students in school and clinical child psychology acquire the needed knowledge and necessary skill set to evaluate students (K-12) and write effective psychoeducational assessment reports. Psychoeducational assessment reports, most of which are conducted by psychologists working in a school setting, are by far the most prevalent form of child psychological evaluation. The lack of availability of a training text on psychoeducational assessment and report writing makes this book a useful resource that fi lls a needed gap in the literature. Existing texts are too broad, offering simultaneous guidance on clinical assessment, psychoeducational assessment, adult assessment, and preschool assessment. The contents of these sources are primarily geared toward students (or practitioners) who seek to work in a private practice, university clinic, or hospital setting and span all age ranges (infant through geriatric). None of the existing books provide suffi - cient coverage of the process of psychoeducational assessment and report writing particularly in relation to the IDEA/state special education classifi cations for which psychologists in the schools will become responsible: learning disabilities, emotional disturbance, autism, intellectual disabilities, and other health impairment. Unlike other volumes, this book presents an approach to assessment and report writing that may be readily adopted by trainers in school and clinical child psychology, understood by professionals and parents alike, and effectively utilized by IEP teams. The book casts a narrow net, seeking to offer specifi c guidance on the practice of psychoeducational assessment and report writing for school-aged children. Because no other books suffi ciently focus on this topic, this text portends to become a useful resource for instructors in school and clinical child psychology who teach coursework on the evaluation of children. It will also be useful to graduate students in those disciplines as well as early career psychologists who wish for a refresher to their knowledge base.
Keywords: Educational tests and measurements; Psychological tests